Levantamento sobre uso de álcool, tabaco e outras drogas, redes de apoio e apoio social entre universitários - Evangelista, Vítor de Morais Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Large number of studies have shown that university entrance may be a period of vulnerability to students, which would result in a potentiation of alcohol and other drugs. Many studies point to the university population as the largest consumers of tobacco, alcohol and other drugs, which underscores the need for more research aimed at the development of prevention and preparation of specific policies aimed at this segment. This research aim to determine the prevalence of use of psychoactive drugs among college students and to investigate their association with social support networks. These networks, as well as become a way of intervention in both the life of the individual and in society, can provide emotional support, information, material and affective forward to some situations of stress, psychological distress and crisis period. It is cross-sectional study using a representative sample of students from the Faculdade de Ciências e Letras de Assis - UNESP. The research used data collected by the application of a multidimensional questionnaire, closed, self-report prepared from the instrument used by the I National Survey, (Alcohol, Smoking and Substance Involving Screening Test – ASSIST, o Rutgers Alcohol Problem Index (RAPI), Fagerstrom Test , the Social Support Scale with Measure Social Network Study Pro-Health Scale and the Brief Pain Psychological Kessler - K10. The results indicate that although among the university, more than half have ever used any type of illegal substance in life, the high levels of social support, in all dimensions (Social Interaction, Affective, Information, Emotional and Material), were high. However, those who are exposed to low affective support are more likely to use moderate / high alcohol and marijuana. Students who do not have relatives to talk to have more chances to use alcohol, get drunk and use marijuana. Another important point is the fact that students who ...

Grande número de pesquisas tem demonstrado que o ingresso à universidade pode se tornar um período de vulnerabilidade aos estudantes, o que resultaria em uma potencialização do consumo de álcool e outras drogas. Muitos estudos apontam a população universitária como os maiores consumidores de tabaco, álcool e outras drogas, o que ressalta a necessidade de um maior número de pesquisas que visem o desenvolvimento de ações de prevenção e elaboração de políticas específicas dirigidas para esse segmento. A presente pesquisa tem como objetivo determinar a prevalência do uso de drogas psicoativas entre estudantes universitários e investigar a sua associação com as redes de apoio social. Essas redes, além de se tornarem uma maneira de intervenção tanto na vida do indivíduo quanto na sociedade, podem proporcionar sustentação emocional, de informação, material e afetiva frente a algumas situações de estresse, crise adaptativa e sofrimento psicológico. Trata-se de estudo transversal com a utilização de amostra representativa de estudantes universitários da Faculdade de Ciências e Letras de Assis – UNESP. A pesquisa utilizou dados coletados por meio da aplicação de um questionário multidimensional, fechado, de autopreenchimento elaborado a partir do instrumento utilizado no I Levantamento Nacional (Alcohol, Smoking and Substance Involving Screening Test – ASSIST, o Rutgers Alcohol Problem Index (RAPI) , Teste de Fagerstrom), a Escala de Apoio Social juntamente com Medida de Rede Social do Estudo Pró-Saúde e a Escala Breve de Sofrimento Psicológico de Kessler – K10. Os resultados indicam que embora mais da metade já tenham consumido algum tipo de substância ilícita na vida, os índices de apoio social foram altos em todas as dimensões (Interação Social, Afetiva, Informação, Emocional e Material). Contudo, aqueles que estão expostos ao baixo Apoio Afetivo estão ...
Keywords: Drogas; Estudantes universitarios - Brasil; Epidemiologia; Saúde pública; Drugs